On Inventory, Production and Employment Scheduling - Schild, A. (Management Science, 1959)
The paper extends results of Holt, Modigliani, Muth and Simon in scheduling over time to minimize costs. It studies generalizations of the cost function which are possible without spoiling the essential simplicity of the decision rules. This is illustrated by a costing model which includes: (a) inventories of individual products, (b) a more realistic treatment of set-up costs, (c) an interest factor to discount future costs, and (d) the cost of additional temporary storage when inventory is high.